A Systematic Mapping Study on Software Testing for Systems-of-Systems - Lopes, Vinicius Carvalho; Norberto, Marcus; S., Douglas Winston R.; Kassab, Mohamad; Soares, Anderson da Silva; Oliveira, Roberto; Graciano Neto, Valdemar Vicente (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2020: Anais do V Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2020)
Context: Smart Cities and other Systems-of-Systems (SoS) have attracted attention due to their potential for innovation in the services provided to the society. SoS are composed of several independent systems and often support critical domains. As such, failures can cause serious damage or even financial losses that can be avoided by performing quality assurance (QA). Among QA techniques, software testing is an essential activity that checks software behaviors against a subset of parameters. However, testing SoS can be even more complex since several other factors further elevate the complexity of the test, such as interoperability links and multiple independent systems. Goal: Our goal in this paper is to analyze the current state of research on software testing for SoS domain. Method: A protocol was formulated and executed according to the guidelines for performing systematic literature mappings in Software Engineering. Results: This study identified the tools, approaches, methods and processes that the literature has addressed to test SoS. Conclusions: Software Testing for SoS still faces several problems and presents many questions to be answered, particularly in the definition of processes and metrics.